Uso de curativo a vácuo como terapia adjuvante na cicatrização de sítio cirúrgico infectado - de Camargo, Paula Angeleli Bueno [UNESP]; Bertanha, Matheus [UNESP]; Moura, Regina [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; de Alvarenga Yoshida, Ricardo [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; de Oliveira Mariúba, Jamil Victor [UNESP]; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2016)
Infections at the sites of surgery involving synthetic prostheses are challenging to treat. We present a case of a patient with multiple comorbidities who had undergone an aortobifemoral bypass 6 years previously and then re-intervention at the femoral anastomoses for restenosis 5 years previously. The patient presented with acute left inguinal pain and swelling and was diagnosed with a ruptured femoral pseudoaneurysm and hemodynamic instability. A repair was conducted by interposition of a silver-coated Dacron graft in the emergency room, and a large abdominal incisional hernia was repaired with synthetic mesh during the same intervention. After surgery, the patient remained intubated in intensive care for a long period. Meanwhile, she presented dehiscence of sutures and a left inguinal purulent fistula that was in contact with the vascular prosthesis. Conservative treatment was chosen, with debridement of wounds and vacuum therapy. The patient improved and the wounds healed. This could be an important tool in similar cases.
Using vacuum therapy as an adjunctive treatment for healing of infected surgical sites
Keywords: Abdominal injury closure techniques; Healing; Infection; Treatment; Vascular prosthesis